2017
DOI: 10.1002/lno.10565
|View full text |Cite
|
Sign up to set email alerts
|

Light availability rather than Fe controls the magnitude of massive phytoplankton bloom in the Amundsen Sea polynyas, Antarctica

Abstract: Amundsen Sea polynyas are among the most productive, yet climate-sensitive ecosystems in the Southern Ocean and host massive annual phytoplankton blooms. These blooms are believed to be controlled by iron fluxes from melting ice and icebergs and by intrusion of nutrient-rich Circumpolar Deep Water, however the interplay between iron effects and other controls, such as light availability, has not yet been quantified. Here, we examine phytoplankton photophysiology in relation to Fe stress and physical forcing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 66 publications
7
59
1
Order By: Relevance
“…The inverse correlation we observed between dFe concentrations and NPP (Figure i) indicates that during spring, phytoplankton were growing on the available dFe, resulting in low dFe concentrations in areas with high NPP. As described above, Park et al () also found that light, instead of dFe, controlled summer phytoplankton biomass in the Pine Island Polynya (Amundsen Sea), consistent with our findings in the WAP. Nearby in Ryder Bay, Annett et al () reported sufficient dFe concentrations for complete macronutrient drawdown, indicating that dFe concentration would not limit phytoplankton growth throughout the growing season.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The inverse correlation we observed between dFe concentrations and NPP (Figure i) indicates that during spring, phytoplankton were growing on the available dFe, resulting in low dFe concentrations in areas with high NPP. As described above, Park et al () also found that light, instead of dFe, controlled summer phytoplankton biomass in the Pine Island Polynya (Amundsen Sea), consistent with our findings in the WAP. Nearby in Ryder Bay, Annett et al () reported sufficient dFe concentrations for complete macronutrient drawdown, indicating that dFe concentration would not limit phytoplankton growth throughout the growing season.…”
Section: Discussionsupporting
confidence: 93%
“…Arrigo et al () showed that net phytoplankton growth occurs in stratified regions with low ice cover, where there is sufficient light in the mixed layer, indicating that in the spring light appears to be the most important factor controlling phytoplankton growth. Similarly, in the Amundsen Sea's Pine Island Polynya, Park et al () found that light rather than dFe controls the magnitude of summer phytoplankton blooms. In both of these cases, dFe was sufficient so as to not limit phytoplankton growth: in the springtime WAP, this was because dFe resupplied during the winter had not yet been fully consumed (this study; Arrigo et al, ); in the summertime Pine Island Polynya, continual glacial melt provided sufficient dFe input so as to not limit growth (Park et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All samples were kept under dim light conditions (ca. 5 μ mol quanta m −2 s −1 ) at in situ temperatures for > 30 min to alleviate the effects of nonphotochemical quenching and photoinhibition (Park et al ). Fluorescence response was analyzed using FPRO Software developed by M. Gorbunov.…”
Section: Methodsmentioning
confidence: 99%